Implementation of the Phase Coding Steganography Method for Embedding Secret Messages in Audio Media - Daniel S. Simbolon; Daniel Adrian Sirait; Stephen Gilbert R. Gulo (Journal Majelis Paspama, 2024)
The development of information technology has driven an increasing need for data security, particularly in the transmission of secret messages through digital media. One technique that can be used to maintain information confidentiality is steganography, which is the method of hiding messages within other media without causing noticeable changes. This study aims to implement the Phase Coding steganography method for embedding secret messages into digital audio media, so that the message is not easily detected by unauthorized parties. The Phase Coding method works by modifying the phase of the audio signal without significantly altering its amplitude, thereby maintaining audio quality and making it difficult to distinguish from the original audio by human hearing. In this study, the process includes preparing the audio file as a cover, converting the secret message into binary form, embedding the message using the Phase Coding technique, and extracting the hidden message. The implementation is carried out using a programming language to test the success of both embedding and retrieving the message. The results show that the Phase Coding method is capable of embedding secret messages into audio media with good performance without significantly degrading audio quality. The secret message can also be accurately extracted and recovered in its original form. Therefore, the Phase Coding steganography method can be considered an effective solution for securing information in audio-based media.